Immunomodulation with β-glucan in matrinxã (Brycon amazonicus) - Franco-Montoya, Luz Natalia [UNESP] (2016)
This study was performed through three experiments and is presented in six chapters. In the first, we present a general introduction on the subject of the thesis and in the last chapter we present the final considerations and thesis conclusions. The other four chapters were written as scientific papers to be submitted to specialized journals. In the first experiment, we tested the innate immune response of juvenile matrinxã Brycon amazonicus fed with two concentrations of β-glucan (β-G) derived from Saccharomyces cerevisiae (0.5% and 1.0%) during 10 days. After feeding, we experimentally infected the fish with an intraperitoneal (IP) injection of Aeromonas hydrophila and sampled the animals prior to and 6 h post infection (hpi). The results showed that β-glucan (0.5%) improved the pre-infection cortisol and lysozyme serum levels and modulated some acute phase proteins on the acute phase response of fish. In addition, we observed that β-glucan (1.0%) led to the exhaustion of innate immune response and can be detrimental to health of fish. In the second experiment, we evaluated two generations of β-glucan, with different levels of purity: MacroGard (β-G 1° 71% pure) and a new generation “R&D β-glucan” (β-G 2° 62% pure). Two groups of fish were supplemented during 15 days with 0.1% of respective generations of β-glucan and at the end of trial fish were challenged with IP injection of A. hydrophila. Fish were sampled prior to, 6, 24, and 72 hpi. Data from this experiment is presented in chapters 3 and 4 of this thesis. The results showed that β-G 2° was more efficient to stimulate both humoral and cellular innate immune responses in fish. However, both β-glucan generations showed an ability to increase pre-infection cortisol and lysozyme serum levels as well as increase the number of circulating neutrophils and monocytes. In addition, the use of β-G 2° was observed to modulate the serum protein profile during acute phase respo nse by bacterial infection of fish. In the third experiment, we discussed the role of serum cortisol levels on the immunostimulant effect of β-glucan. To this end, we fed fish during 15 days with diets containing β-glucan 0.1% only (β-G) or β-glucan 0.1% + metyrapone 30mg kg -1 fish (β-G+MTP). Dietary MTP was used to block the cortisol production. The fish were then submitted to 3 min of air exposure as an acute stressor and , following that, challenged with an IP injection of A. hydrophila. Fish were sampled prior to stress conditions, 30 min after stressor exposure and 24 hpi. The results showed that β -G modulated the cortisol profile prior to and after stress response, and increased both the number and activity of leukocytes. Furthermore, cortisol was shown to be a strong modulator of both humoral and cellular innate immune mechanisms, since it increased the lysozyme and complement activity as well as the neutrophils and monocytes populations. Our results suggest that β-glucan-induced cortisol level is one important mechanism to improve the innate immune response to β-glucans in matrinxã. Finally, we propose a protocol of immunestimulation for juvenile matrinxã. The addition of β-glucan derived from the cell wall of Saccharomyces cerevisiae can be offered to the fish before management practices. The proposed protocol aims to strengthen fish defense mechanisms, reduce disease outbreak and enhance fish resistance, generating a nutritional product of high quality and safety.